2015
DOI: 10.2174/1570161113666150923111329
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory strategies in stroke: a potential therapeutic target

Abstract: Stroke is an acute condition characterized by a sudden decrease in blood flow to brain tissue, resulting in immediate deprivation of both glucose and oxygen. Different mechanisms are involved in the pathogenesis of stroke, but increasing evidence suggests that one of the processes worsening clinical outcome is inflammation with the synthesis and the release of pro-inflammatory cytokines that activate several cells contributing to the progression of brain injury. Monoclonal antibody therapy has proved useful an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 120 publications
0
30
0
1
Order By: Relevance
“…Glial cell size was increased in the multiparous brain after stroke, suggesting that parity can chronically alter cellular cytoarchitecture and prime microglia toward an M2-like activation state following injury. Whereas depressive behavior and deficits in hippocampal neurogenesis are often associated with systemic immunosuppression in the postpartum period (32), it is well established that antiinflammatory environments and M2-like polarization of activated microglia generally favor positive outcomes following ischemic stroke (33). Consistent with this understanding, others have found that peritoneal macrophages from primiparous females exhibited less of a PMA-induced oxidative burst than nulliparous macrophages (34).…”
Section: Discussionmentioning
confidence: 93%
“…Glial cell size was increased in the multiparous brain after stroke, suggesting that parity can chronically alter cellular cytoarchitecture and prime microglia toward an M2-like activation state following injury. Whereas depressive behavior and deficits in hippocampal neurogenesis are often associated with systemic immunosuppression in the postpartum period (32), it is well established that antiinflammatory environments and M2-like polarization of activated microglia generally favor positive outcomes following ischemic stroke (33). Consistent with this understanding, others have found that peritoneal macrophages from primiparous females exhibited less of a PMA-induced oxidative burst than nulliparous macrophages (34).…”
Section: Discussionmentioning
confidence: 93%
“…69 Hu et al 34 found that macrophage subtype shifted from early beneficial M2 microglia to M1 microglia and suggested that new therapies should focus on adjusting the balance between good and bad subtypes. Recently, this shift from the M1 to the M2 phenotype in stroke was found to be mTOR mediated.…”
Section: Inflammatory/stress Response and Immune Modulationmentioning
confidence: 99%
“…One explanation is that rodents' and humans' inflammatory responses post-stroke involve different integrins and signaling responses. 69 Remote ischemic preconditioning has been found to protect against focal ischemia and preserve neurological function via ameliorating postocclusion reduction in CD3+/CD8+ T cells and CD3+/ CD161a+ natural killer T cells. It induces interleukin-6 expression and tumor necrosis factor-α expression while increasing the number of noninflammatory monocytes (CD43+/CD172a+).…”
Section: Inflammatory/stress Response and Immune Modulationmentioning
confidence: 99%
“…Infection or high levels of proinflammatory biomarkers indicate significantly increased risk of ischemic stroke, especially in the elderly. [8][9][10] The onset or worsening of a stroke in these patients could be caused either by direct damage of the CoVs on the nervous system and/or by an activation of the mechanisms of COVID-19 inflammation induced as well coagulation disorders. As the disease spreads and new evidence emerges, we need to identify the existence of additional pathophysiological mechanisms of stroke in COVID-19 patients.…”
mentioning
confidence: 99%